2018
DOI: 10.1021/acsmacrolett.8b00847
|View full text |Cite
|
Sign up to set email alerts
|

Surface Density Variation within Cyclic Polymer Brushes Reveals Topology Effects on Their Nanotribological and Biopassive Properties

Abstract: While topology effects by cyclic polymers in solution and melts are well-known, their translation into the interfacial properties of polymer “brushes” provides new opportunities to impart enhanced surface lubricity and biopassivity to inorganic surfaces, above and beyond that expected for linear analogues of identical composition. The impact of polymer topology on the nanotribological and protein-resistance properties of polymer brushes is revealed by studying linear and cyclic poly­(2-ethyl-2-oxazoline) (PEOX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 57 publications
(72 reference statements)
0
57
0
Order By: Relevance
“…Based on the results described above, it is demonstrated that although they share the same chemical composition, the cyclic and linear PIL brushes may exist as multilayer films on gold surfaces and have substantially different surface morphologies and surface graft density (i.e., charge density), which possibly account for the enhanced bactericidal performance observed in the cyclic PIL brushes. Actually, the recent studies by Benetti and coworkers have demonstrated that by tailoring the size of cyclic poly(2‐ethyl‐2‐oxazoline), one can control the surface of functional materials with special physico‐chemical properties . Based on these studies, we suggested that the bactericidal activity of cyclic brushes could be potentially tunable by varying the size of cyclic PIL brushes.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…Based on the results described above, it is demonstrated that although they share the same chemical composition, the cyclic and linear PIL brushes may exist as multilayer films on gold surfaces and have substantially different surface morphologies and surface graft density (i.e., charge density), which possibly account for the enhanced bactericidal performance observed in the cyclic PIL brushes. Actually, the recent studies by Benetti and coworkers have demonstrated that by tailoring the size of cyclic poly(2‐ethyl‐2‐oxazoline), one can control the surface of functional materials with special physico‐chemical properties . Based on these studies, we suggested that the bactericidal activity of cyclic brushes could be potentially tunable by varying the size of cyclic PIL brushes.…”
Section: Methodsmentioning
confidence: 85%
“…In particular, the Benetti group studied how the topology effects typically displayed by cyclic poly(2‐ethyl‐2‐oxazoline) (PEOXA) in solution manifested for brush assemblies generated on surfaces. It was demonstrated that the topological effects of the brush assemblies imparted by the cyclic polymer architecture translated into an enhancement of the brush properties, such as steric stabilization of surfaces, antifouling and lubricating behavior . Inspired by these advances, in this study, we focused on the preparation of cyclic PIL brushes by the “grafting to” technique and systematically compared the bactericidal activity of linear brush analogs.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, cyclic PAOXA adsorbates are characterized by reduced molecular dimensions with respect to their linear counterparts of comparable molecular weight, [55,56] and thus can form denser brush layers when assembled on solid surfaces from diluted solutions. [57][58][59][60] In addition, due to the constraints introduced during their cyclization, [61] cyclic PAOXA grafts generate films that provide an augmented steric stabilization of the surface, when compared to linear-brush analogues (Figure 6a). [59,62] Hence, the unique properties and intrinsic structure of cyclic brushes enabled the fabrication of PAOXA surfaces with significantly enhanced biopassivity with respect to that typically displayed by linear PAOXA-based analogues.…”
Section: Topology Of Paoxas At Surfacesmentioning
confidence: 99%
“…[57 -59] Similarly to their PEG-based analogues, poly(2ethyl-2-oxazoline) (PEOXA) brushes assembled on TiO 2 surfaces ( Figure 4) show a lubricious character that is strictly correlated with their surface coverage (expressed as grafting density, Σ, in Figure 4). [60,61] The characterization of the nanotribological properties of PEOXA brushes by lateral force microscopy (LFM) [62] has further highlighted the effect of chain interdigitation in determining friction between brushbearing surfaces. As shown in the friction force-vs.applied load (F f L) profiles reported in Figure 4,b, when PEOXA brushes are sheared against an identical brush countersurface, friction is generally lower for all grafting densities investigated, compared to the case where the same brushes are slid past a bare TiO 2 surface.…”
Section: Alternatives To Peg Brushesmentioning
confidence: 99%
“…This phenomenon was due to the absence of linear chain ends within cyclic brushes, which hinders interpenetration between opposing grafts [81] and markedly reduces dissipative forces that are typically responsible for the increment in friction observed between linear brushes at relatively high applied loads. [60,61]…”
Section: Effect Of Brush Architecture On Protein Resistance and Lubrimentioning
confidence: 99%